Use of evaporative cooling systems and their effects on core body temperature and lying times in dairy cattle - Johnson, Jared (Kansas State University, 2015)
Study 1 was performed to assess the effect of an evaporative cooling system (ECS) on core body temperature (CBT) and lying times in lactating dairy cows. Respiration rates and rear udder temperatures (T[subscript u]) were also measured. Trial 1 contained 3 environmental treatments while trial 2 contained 2 environmental treatments. Treatments were: OFF (Cyclone fans and fog shut off), FAN (Cyclone fans only, no fog), and FANFOG (Cyclone fans and fog on) and cows exposed to these 3 environments were housed in a bedded pack barn (PACK) equipped with an ECS or a tie-stall barn (TIE). TIE and PACK cows moved between barns every 8 h for milking and both groups moved opposite of each other. Ambient, barn temperature and relative humidity (RH) measurements in addition to vaginal temperatures and lying times were recorded by sensors which took measurements at 1 min intervals. Respiration rates (BPM), for PACK cows during FANFOG were reduced (P < 0.05) when compared to TIE (53 ± 2.0 vs 64 ± 2.0, respectively) in trial 1. Similar results were found in trial 2. Rear udder temperature was measured and found to be decreased (P < 0.05) in PACK cows while housed under FANFOG vs TIE in trial 1. These results could not be repeated in trial 2 because of greater ambient temperatures. Core body temperature (CBT) was reduced during each trial as shown by less time spent above 39.0°C during FANFOG. During trial 2, PACK spent 5.7 and 8.5 h/d less over a CBT of 39.0°C compared to TIE cows. Total daily lying time was tracked and found to increase for cows exposed to the ECS during PACK but no difference between PACK and TIE. In study 2, the same ECS was used but its effects on nonlactating dairy cows were studied. There was a treatment by h interaction for vaginal temperature showing the greatest effects during the afternoon h where FANFOG had numerically decreased CBT vs FAN. FANFOG cows spent reduced time over a CBT of 39.0°C and greater time < 38.0°C. FANFOG cows also had increased lying times of 1.7 h/d compared to FAN.
Keywords: Heat stress; Evaporative cooling; Core body temperature; Lying behavior; Agriculture, General (0473); Animal Sciences (0475)